(untitled) (Universal International Scientific Journal, 2026)
This thesis examines the integration of differentiated instruction with artificial intelligence (AI) and digital technologies in developing university students’ reading and writing skills in English. Differentiated instruction addresses learners’ individual needs, proficiency levels, and learning styles, enabling more inclusive and effective language instruction. The study emphasizes that technological integration alone is insufficient without a strong pedagogical foundation. Therefore, motivational, identity-based, and learner-centered approaches are incorporated to enhance students’ engagement and investment in language learning. AI-supported digital tools provide personalized feedback, adaptive learning pathways, and opportunities for autonomous practice. The findings suggest that combining differentiated instruction with AI and motivational pedagogical approaches significantly improves students’ academic performance, self-confidence, and active participation in English reading and writing tasks.